Building a successful board-test strategy - Scheiber, Stephen F. (Boston : Butterworth-Heinemann, 2001)
Written in a clear and thoughtful style, Building a Successful Board-Test Strategy, Second Edition offers an integrated approach to the complicated process of developing the test strategies most suited to a company's profile and philosophy. This book also provides comprehensive coverage of the specifics of electronic test equipment as well as those broader issues of management and marketing that shape a manufacturer's "image of quality." In this new edition, the author adds still more "war stories," relevant examples from his own experience, which will guide his readers in their decisionmaking. He has also updated all technical aspects of the first edition, covering new device and attachment technologies, new inspection techniques including optical, infrared and x-ray, as well as vectorless methods for detecting surface-mount open-circuit board failures. The chapter on economics has been extensively revised, and the bibliography includes the latest material on this topic. *Discusses ball-grid arrays and other new devices and attachment technologies *Adds a comprehensive new chapter on optical, infrared, and x-ray inspection *Covers vectorless techniques for detecting surface-mount open-circuit board failures.
Part I: Strategies and Tactics; Part II: Making the Job Easier; 7. Environmental-Stress Screening; Part III: Creating Test Solutions; Part IV: Pulling It All Together; Appendix.
"Test & measurement world"--Cover.
Includes bibliographical references (p. 321-328) and index.
Keywords: Printed circuits -- Testing; Electronic books